Rancang Bangun Monitoring Suhu dan pH Air Kolam Pembenihan Udang Vaname Berbasis Android - Mauliddin, Akhmad (Journal of Telecommunication Network (Jurnal Jaringan Telekomunikasi), 2018)
The factors that cause the death of vannamei shrimp seeds include water temperature and acidity of water pH. The need for water temperature for vaname shrimp hatcheries ranges from 28 ° C to 32 ° C and the acidity level of the vaname shrimp hatchery water ranges from 7 to 8.3 . It is difficult to know what changes in water temperature and pH have occurred because there is no technology that can support it. The design offered is in the form of monitoring the temperature and pH of the water in the vaname shrimp hatchery so that it is more effective because it can be done remotely. This application works with a temperature sensor and a pH sensor that reads the temperature and pH of the water in the vaname shrimp hatchery continuously. So, when the temperature and pH change far from normal temperature and pH in the range of 28 ° C to 32 ° C, the read temperature and acidity (pH) will be processed on the microcontroller, then the data from the microcontroller will be sent to the ethernet shield then it will be displayed in the android application. With this application, it is hoped that the owner of the vaname shrimp hatchery can monitor and take action on changes in water temperature and pH that occur continuously. Thus, the possibility of the vaname shrimp seed mortality factor can be reduced.